Multi-viewpoint ontological representation of composite concepts: a description logics-based approach. (2017) - Hemam, Mounir; Djezzar, Meriem; Boufaida, Zizette
A real world entity is unique but it can have several representations, due to various interests or perspectives, that we cannot conceive using classical ontological languages. We are interested in the problem of multi-representation in ontologies. We believe that the most appropriate way is to use viewpoint notion in order to build ontologies called 'multi-viewpoints ontologies'. In this paper, we introduce the notion of composite concept in a multi-viewpoint ontological model based on description logic (DL) formalism. Composite concepts are compositions of others concepts. The use of viewpoint notion in the representation of a composite concept entails consequences on the decomposition of the latter. In fact, two observers looking at the same concept can see two different sets of components, giving rise to multiple decompositions. So, our goal is to propose an ontological language, named VpCo-DL, which extend DL language, to support multi-viewpoints representation of composite concepts and their components. Both syntax and semantics of the extended language are considered. Illustrative examples are given.